Textile wastewater challenges and current mitigation methods: an overview - Bellow, Ibrahim Adebayo; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Alkhatib, Ma'an Fahmi Rashid (International Islamic University Malaysia, 2016)
Effluents from dye and textile industries are highly contaminated and toxic to the environment. High concentration of non-biodegradable compounds contributes to increased biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of the wastewater bodies. Dyes found in wastewater from textile industries are carcinogenic, mutagenic or teratogenic. Biological processes involving certain bacteria, fungi, activated carbon and carbon nanotubes (CNTs) are promising methods for treating the waste water. These methods are either inefficient or ineffective. These complexities necessitates search for new approaches that will offset all the shortcomings of the present solutions to the challenges faced with textile wastewater management. This article reviews the past and recent methods used in the treatment of the textile dye wastewater and the future opportunities for efficient treatment of textiles wastewaters.